Estimation of marine shale methane adsorption capacity based on experimental investigations of Lower Silurian Longmaxi formation in the Upper Yangtze Platform, south China. (December 2015) - Ji, Wenming; Song, Yan; Jiang, Zhenxue; Chen, Lei; Li, Zhuo; Yang, Xiao; Meng, Mianmo
Abstract: Methane adsorption experiments were performed on eight Lower Silurian Longmaxi moisture-equilibrated shale samples from the Upper Yangtze Platform, south China, at pressures up to 12 MPa, at 20 °C, 40 °C, 60 °C, 80 °C and 100 °C to investigate the effects upon methane adsorption capacity and to estimate the variation of methane adsorption capacity as a function of depth and burial history. The methane adsorption capacity of the Longmaxi shale shows a significant positive correlation with total organic carbon (TOC) content, which is accompanied by an increase in BET (Brunauer Emmett Teller) surface area and total pore volume. A quadratic relationship was observed between clay content and methane adsorption capacity. There is a threshold clay content (42.3–44.4%) in this trend. Methane adsorption capacity declines with increasing clay content below the threshold, and later increases with increasing clay content. The Langmuir pressure decreases exponentially with the reciprocal of temperature and the Langmuir volume decreases linearly with temperature. The isosteric heat of adsorption and standard entropy for the Longmaxi shale ranges from 10.34 to 11.67 kJ/mol and from −57.04 to −61.32 J/mol/K, respectively, which are clustered around kerogen type I. Using these relationships a computational scheme was developed to calculate methane adsorption capacity as a function of TOC content, temperature and pressure based on the Langmuir equation. This algorithm was applied to estimate methane adsorption capacity of the Longmaxi shale as a function of depth. Due to the dominating effect of pressure methane adsorption capacity increases initially with depth, through a maximum and then decreases as a result of increasing temperature at a greater depth. The maximum gas adsorption capacity is typically located at a depth range between 800 and 1350 m. With TOC content increasing, the curves shift continuously towards higher adsorption capacity. Furthermore, the maximum methane adsorption capacity moves higher and shifts to a deeper depth as TOC content increases. Ultimately, four principal dynamic evolutionary stages of methane adsorption capacity of the Longmaxi shale over geologic time as a function of burial history were reconstructed. Graphical abstract: Evolution of CH4 sorption capacity of Longmaxi shale as a function of burial history. Highlights: The key effects on CH4 sorption capacity in Longmaxi shale are TOC content, temperature and pressure. The thermodynamic parameters of CH4 sorption on Longmaxi shale are consistent with type I kerogen. CH4 sorption capacity estimation algorithm was developed based on Langmuir equation. CH4 sorption capacity as a function of depth and burial history were established, respectively.